2022
DOI: 10.3389/fcell.2022.809996
|View full text |Cite
|
Sign up to set email alerts
|

Higenamine Attenuates Doxorubicin-Induced Cardiac Remodeling and Myocyte Apoptosis by Suppressing AMPK Activation

Abstract: Background: As an effective antitumor drug, doxorubicin (DOX) is primarily used to treat solid tumors and hematologic malignancies. However, increasing evidence has emerged indicating its cardiotoxicity, and few solutions have been proposed to counter this side effect. Higenamine (HG) is a natural compound widely found in many Chinese herbs and also serves as a component in many healthcare products. Several studies have demonstrated its cardioprotective effect in different models, but little is known about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The hearts were extracted from 2- to 3-day-old Sprague-Dawley rat pups of both genders (SIPEIFU, Beijing, China) following previously established protocols [ 18 ]. The extracted hearts were rinsed in HBSS (Solarbio, Beijing, China) and subjected to multiple digestions using 0.05 % trypsin (BI, Shanghai, China) and 0.15 % type II collagenase (Worthington, NJ, USA) in HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…The hearts were extracted from 2- to 3-day-old Sprague-Dawley rat pups of both genders (SIPEIFU, Beijing, China) following previously established protocols [ 18 ]. The extracted hearts were rinsed in HBSS (Solarbio, Beijing, China) and subjected to multiple digestions using 0.05 % trypsin (BI, Shanghai, China) and 0.15 % type II collagenase (Worthington, NJ, USA) in HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier study found that the administration of HG significantly decreased Caspase three activity, Bax expression, and Cyto-C release, while upregulated Bcl-2 expression before rats underwent I/R injury ( Lee et al, 2006 ). Furthermore, research has indicated that HG can attenuate DOX-induced cardiac remodeling and myocyte apoptosis by suppressing AMPK activation ( Jin et al, 2022 ). Another in-depth study found that HG counteracted apoptosis and protected against I/R-induced MI in rat cardiomyocytes by activating β2-AR and the β2-AR/PI3K/AKT signaling pathway ( Wu M. P. et al, 2016 ).…”
Section: The Potential Impact Of Yyfz On Mitochondria-er Interactionsmentioning
confidence: 99%
“…RES and matrine attenuated CMs apoptosis via the AMPK pathway ( 124 , 125 ). Higenamine, the main active component of the TCM Wu-Tou, also attenuates DOX-induced cardiac remodeling and myocyte apoptosis by suppressing AMPK activation ( 126 ) ( Figure 4 ).…”
Section: Molecular Mechanisms Of Chemoradiotherapy-related Cardiotoxi...mentioning
confidence: 99%